ANALYSIS OF ROUTINE STRESS TESTING AFTER PCI IN PATIENTS WITH AND WITHOUT ACUTE CORONARY SYNDROME - AHMAD, I; AKHTAR, S; QURESHI, RA; ADIL, M; REHMAN, IU; ALI, Z; ANSAR, R (Biological and Clinical Sciences Research Journal, 2024)
Routine stress testing post-percutaneous coronary intervention (PCI) is critical in managing coronary artery disease (CAD) patients. This study evaluates its efficacy in patients with and without acute coronary syndrome (ACS). Objective: To assess the clinical outcomes and cost-effectiveness of routine stress testing following PCI in patients with and without ACS. Methods: A retrospective cohort study was conducted with 300 patients who underwent PCI. The cohort was divided into ACS (n=150) and non-ACS (n=150) groups. Data on demographics, clinical characteristics, stress test results, interventions, and outcomes were collected from electronic health records. The primary outcome was the incidence of major adverse cardiac events (MACE). Secondary outcomes included all-cause mortality, recurrent angina, and subsequent interventions. Statistical analyses included chi-square tests, t-tests, Kaplan-Meier survival analysis, and Cox proportional hazards regression. Results: The average age was 63.5 ± 10.2 years for ACS and 65.2 ± 11.3 years for non-ACS patients (p=0.045). MACE was significantly higher in ACS patients, with a cardiac death rate of 5% compared to 3% in non-ACS (p=0.034). ACS patients had a higher prevalence of abnormal stress tests (40% vs. 35%, p=0.389) and required more interventions, including repeat PCI and CABG. Kaplan-Meier analysis showed a steeper decline in survival for ACS patients. Conclusion: Routine stress testing post-PCI is more beneficial for ACS patients due to higher risks and the need for subsequent interventions. However, its routine use in non-ACS patients is less clear, suggesting tailored approaches based on individual risk profiles are needed.